The development of an achievement test in beginning Spanish - Cauayani, Consejo V. (Education quarterly.)
This paper has presented three topics. First, recognition is given to the need for evaluation measurements, specifically of tests in education. Second, test development is discussed with the use of Two-Dimentional Chart, the preparation of an item pool and the revision of test items into its final form. The Third topic, test analysis, includes the try-out to get at bits of information, namely, the Difficulty Index and Discrimination Index required to determine the extent of test relevance for the college tests in beginning Spanish. A final criterion of test relevance is determined in the use of the whole test with students of known achievement level in Spanish. If students with high ability in Spanish generally do well in the achievement test, the test has indications of high relevance.